الصعوبات التي تواجه أساتذة المواد العلمية بمرحلة التعليم المتوسط في تطبيق استراتيجية حل المشكلات - عمرون, سليم; زين, إبراهيم; حريزي, بوجمعة (جامعة الوادي - University of Eloued, 2022)
هـــدفت الدراســـة الحاليـــة إلـــى الكشـــف عـــن الصـــعوبات التـــي تواجـــه أســـاتذة المـــواد العلميـــة بمرحلـــة التعلـــيم المتوســـط فــــي تطبيق اســــتراتيجية حـــل المشــــكلات، والفـــروق فــــي هــــذه الصـــعوبات بــــين الأســــاتذة تبعــــا لمتغيــــري الجـــــنس والأقدميــــة المهنيـــــة، واستخدم المـــــنهج الوصـــــفي، كما اســـتخدم فـــي جمـــع البيانات اســـتبيان صـــعوبات تطبيق اســـتراتيجية حـــل المشـــكلات المعـــد مـــن طـــرف البـــاحثين، وتم تطبـــيقه علـــى عينـــة عشـــوائية بســـيطة تتكـــون مـــن 19 أســـتاذا (7ذكور- 12أنثـــى) يدرســـــون بمتوسطات مدينة المســـــيلة أثنـــــاء الموســـــم الدراســـــي (2020-2021). وتوصلت الدراســـة إلى أن أســـاتذة المـــواد العلميـــة بمرحلـــة التعلـــيم المتوســـط يواجـــهون صـــعوبات فـــي تطبيق اســـتراتيجية حـــل المشـــكلات مصـــدرها التلميــذ والمنهـــاج الدراســـي بدرجـــة أكبـــر مـــن الصـــعوبات التــــي يكــــون مصــــدرها الأســــتاذ ــــــ لا توجــــد فروقــــا دالــــة إحصــــائيا فـــي الصـــعوبات التــــي تواجــــه أســـاتذة المـــواد العلميـــة بمرحلـــة التعلـــيم المتوســـط في تطبيق اســـتراتيجية حـــل المشـــكلات تعـــزى لمتغيـــري الجنس والأقدمية المهنية. Abstract : The present study aimed to reveal the difficulties faced by teachers of scientific subjects stage intermediate education in the application of problem-solving strategy, and the differences in these difficulties between the teachers on the variables of sex and Professional Experience, and use descriptive approach, as used in data collection application difficulties questionnaire strategy to solve problems prepared The researchers' party, and it was applied to a simple random sample of 19 teachers (7 males - 12 females) studying with some middle schools of M'sila during the academic season (2020-2021). The study found that the teachers of scientific subjects in the intermediate education stage are facing difficulties in implementing a problem-solving strategy that comes from the student and the curriculum to a greater degree than the difficulties that come from the teacher. There are no statistically significant differences in the difficulties faced by teachers of scientific subjects in the intermediate education stage in applying a strategy to solve problems according to the variables of sex and professional experience
دراسة ميدانية بمتوسطة محمد الصديق بن يحي بالمسيلة
مقال
Keywords: الصعوبات؛ استراتيجية حل المشكلات؛ أساتذة المواد العلمية; Difficulties; Problem-solving strategy; teachers of scientific subjects